2011
DOI: 10.1136/oemed-2011-100382.250
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for computer vision syndrome among operators of two call centres in Sao Paulo, Brazil

Abstract: The aim of this study was to estimate the prevalence of Computer Vision Syndrome (CVS) among operators from two call centres located in São Paulo (n=476). Methods and results The symptoms were: visual fatigue (73.9%), "heaviness" in the eyes (68.2%), "burning" eyes (54.6%), tearing (43.9%) and vision impairment (43.5%). Other associations were: being female (OR 2.6, 95% CI 1.6-4.1), lack of recognition during work (OR 1.4, 95% CI 1.1 to 1.8); organisation of work in telemarketing (OR 1.4, 95% CI 1.1 to 1.7) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In our study females were more likely to have mild to moderate headaches ( P = .001) and shoulder pain than males ( P = .004). This may be associated with shorter stature affecting their arms, wrists and reach which may affect the reading distance from a hand‐held computer or their height on a desk mounted computer requiring them to have a chin up position, increasing musculoskeletal symptoms . This was not studied in our study and may be an opportunity for future research.…”
Section: Discussionmentioning
confidence: 99%
“…In our study females were more likely to have mild to moderate headaches ( P = .001) and shoulder pain than males ( P = .004). This may be associated with shorter stature affecting their arms, wrists and reach which may affect the reading distance from a hand‐held computer or their height on a desk mounted computer requiring them to have a chin up position, increasing musculoskeletal symptoms . This was not studied in our study and may be an opportunity for future research.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,4 Prior to the COVID-19 Pandemic lockdown in March 2020, many studies looked at the prevalence of CVS within different populations, ranging from the general population to office workers. [5][6][7][8][9][10][11][12][13][14][15][16] The 2016 Digital Eye Strain report compiled survey responses from over 10,000 US adults found an overall self-reported CVS symptom prevalence of 65%. 6 Portello et al surveyed a cohort of 520 office workers in New York City and found that nearly 40% reported the symptom of "tired eyes" and 30% reported the symptoms of "dry eyes" and "eyestrain" occurring "at least half of the time" during a given week.…”
Section: Introductionmentioning
confidence: 99%